The Effectiveness of Giving Fe Tablets to Pregnant Women to Prevent Anemia - Husna, Putri Halimu; Romadanish, Tiara (Jurnal AKPER GSH, 2021)
Background: Anemia in pregnant women often occured because fetal oxygen need in the womb increased so that the hemoglobin level needed to bind blood in pregnant women must increase. Giving Fe tablets was one of the government programs to prevent anemia. Goals: Knowing the effect of consumption of Fe tablets on the level of anemia in pregnant women. Methods: This study used with a case study research approach. Population: The population used in this study were all third trimester pregnant women in Purworejo Village, Wonogiri who were willing to become research informants with a total of 3 informants. The instruments: Observation sheets, Fe tablets, notebooks/stationery. The tools used in this study were the Easy Touch GCHb Tool, Alcohol swab, Hb meter stick, lancet needle, measuring tape, body scale. Test data analysis: interviews and observations. Results: The results of this study showed that 2 of 3 informants experienced an increase in hemoglobin levels in their blood, and 1 of 3 informants experienced mild anemia after being given the action of giving Fe tablets. 1 of 3 informants experienced a decrease in hemoglobin levels in their blood but they were still within normal limits. Conclusion: The conclusion of this study is that the administration of Fe tablets can affect the third trimester pregnant women in preventing anemia. The administration of Fe tablets with tea and non-adherence to taking Fe tablets on the incidence of anemia need to be investigated further.